Comparison of body mass index and lipid accumulation product as a better indicator of metabolic syndrome - S., Yashavanth H.; S., Bharath M. (International Journal of Advances in Medicine, 2017)
Background: Metabolic syndrome (MS) is defined to be cluster of metabolic interrelated risk factors of such as obesity, elevated blood pressures, glucose metabolism disturbances and dyslipidemia. "Lipid accumulation product" (LAP) – is a simple and novel index based on a combination of an anthropometric dimension and a metabolic dimension. Methods: One hundred patients with metabolic syndrome were included in study. Data was collected through a prepared proforma which included various parameters related to history, thorough clinical examination, and laboratory parameters. Further the patients were assessed for the body mass index (BMI) and lipid accumulation product (LAP). BMI and LAP then correlated with metabolic syndrome. Results: Our present study is conducted among the population meeting the IDF criteria of MS, with a mean age of 54.52±12.65years and female predominance (54%). 72% and 62% of the study group had Diabetes Mellitus and Hypertension respectively. The mean BMI in our study is 29.04±5.11 kg/m2 with 25% of the population are non-obese. The average LAP value in our present study is 111.51±59.71 cm mmol/l and shown increasing trend with increasing age. LAP had a mean value of 85.19 cm mmol/l, 118.52 cm mmol/l and 122.37 cm mmol/l in the study population satisfying 3/5, 4/5 and 5/5 criteria of Metabolic Syndrome respectively. This shows LAP (P<0.001) has better correlation with MS when compared to BMI (P<0.001) in ANOVA test. In our present study, the presence of diabetes mellitus resulted in significant elevated LAP values i.e. 85.10±31.40 cm mmol/l among non-diabetics to 121.78±64.92 cm mmol/l among diabetics, which is of statistical significance (p value 0.005). Conclusions: LAP showed strong positive correlation with metabolic syndrome and it also positively correlated with increasing number of components of metabolic syndrome. LAP found to be better predictor of MS than BMI.